Vis-NIR Broadband Foldable Photodetector Based on the WS2/PANI Composite - Shah P.V.; Detroja D.; Anuraag N.S.; Prasad N.K.; Pataniya P.M.; Sumesh C.K. (My University, 2025)
Large-area broadband photodetectors are required due to technological advancements in the fields of optical communication, military applications, remote communication, and environmental monitoring. Additionally, wearable and flexible electronics are becoming more and more popular every day. Wearable device applications are limited by the fact that a majority of fast, broadband photodetectors are based on rigid substrates. Biodegradable photodetectors that are primarily based on paper have slow response times, typically a few seconds or even tens of seconds. In the current work, paper-based WS2:polyaniline (PANI) composite photodetectors were created to improve their performance. The WS2:PANI composite and pure WS2 were deposited on photocopy paper using a simple hand-printing technique. These hand-printed composite devices exhibit a photoresponse that is nearly 2 orders of magnitude greater than that of pure WS2 and demonstrate broadband photodetection in the wavelength range of 390-1100 nm. The devices exhibit quick response times that range from 290 to 600 ms. By examining the photoresponse for the bending configuration and that after multiple bending cycles, the device’s flexibility and foldability were further investigated. Considering how quickly technology is developing these days and how much waste electronics are produced, switching to paper-based devices could help meet sustainability goals even more. © 2024 American Chemical Society.